Cluster ensemble selection based on validity index in evidence space - Kai BI; Xiao-dan WANG; Ya-qiong XING (Tongxin xuebao)
At first,the concept of evidence space was proposed to overcome the weakness of distance space for describing the complex structure of data sets.And then,the Davies-Bouldin index was extended based on the evidence space proposed.Meanwhile the label-correlation matrix was used to measure the difference of clusters members.At last,the cluster members with better effectiveness and bigger differences were selected for cluster ensemble.The experimental results show that the proposed method is able to improve the effectiveness of cluster ensemble.